Music of a Thousand Years A New History of Persian Musical Traditions - Lucas, Ann E. (University of California Press, 2019)
Iran's particular system of traditional Persian art music has been long treated as the product of an ever-evolving, ancient Persian culture. In Music of a Thousand Years, Ann E. Lucas argues that this music is a modern phenomenon indelibly tied to changing notions of Iran's national history. Rather than considering a single Persian music history, Lucas demonstrates cultural dissimilarity and discontinuity over time, bringing to light two different notions of music-making in relation to premodern and modern musical norms. An important corrective to the history of Persian music, Music of a Thousand Years is the first work to align understandings of Middle Eastern music history with current understandings of the region's political history. "Ann E. Lucas very effectively combines historical analysis, ethnomusicology, and musicology to provide a broad, holistic explanation for complex, nuanced processes of change. Well written and highly original in its approach, this is a major contribution to the field." KAMRAN SCOT AGHAIE, Associate Professor of Iranian History, University of Texas "Music of a Thousand Years presents an innovative narrative of Persian music history and also provides important new perspectives on how to analyze the meaning of music and culture in historical perspective." MOHSEN MOHAMMADI, Lecturer in Ethnomusicology, University of California, Los Angeles "Lucas turns the standard history of Persian music on its head, proving it is not a story of the survival of an ancient tradition, but rather the story of the invention of tradition. Revisionist in the best sense of the word." JAMES L. GELVIN, author of The Modern Middle East: A History ANN E. LUCAS is Assistant Professor of ethnomusicology in the Department of Music at Boston College, where she also teaches in the Islamic Civilizations and Societies Program. She is recognized for her work on music historiography of the Middle East.